Reproductive biology mimus Octupus Octopus (Mollusca: Cephalopoda) in the region of Matarani, Arequipa, Peru - Ishiyama, Victor (1999)
Monthly random samplings (n = 25) were taken from May 1995 to April 1996 in Matarani port, Arequipa (10°59'40" South and 72° 06'13" West). They were shown to be gonochoric and to have sexual dimorphism (the male has an arm for copulation). The sex proportion was 2,1:1,0 (male: female); eight stages of the oocyte development were also found during oogenesis. According to their reproductive behavior, the following maturity gonadic scale was established: a) undifferentiated, b) immature, c) maturation beginning, d) developing, e) mature, f) copula, g) postcopula, autofecundation and evacuation, h) postevacuation. Mature females were preferentially found in spring and summer; mature males at the end of the spring and summer; copulation occurred during summer; autofecundation and evacuationof the eggs were evident in August (50%), October (50%), November (71,4%), December (33%) and January (33%). The first maturity in males was found at 9,5 cm and in the females at 12,5 cm of dorsal length of the body. Some females showed oocytes in lysis and with advanced oogenesis beginning of a new cycle, which demonstrates that not all female die after taking care of the eggs until the final hatching.